Complexity Measures: Open Questions and Novel Opportunities in the Automatic Design and Analysis of Robot Swarms - Roli, Andrea; Ligot, Antoine; Birattari, Mauro (Frontiers in Robotics and AI, 2019)
Complexity measures and information theory metrics in general have recently been attracting the interest of multi-agent and robotics communities, owing to their capability of capturing relevant features of robot behaviours, while abstracting from implementation details. We believe that theories and tools from complex systems science and information theory may be fruitfully applied in the near future to support the automatic design of robot swarms and the analysis of their dynamics. In this paper we discuss opportunities and open questions in this scenario.